PTH-097 Outcome of Pregnancy in Patients with Known Budd-Chiari Syndrome. (17th August 2016) - Khan, F; Rowe, I; Tripathi, D; Mehrzad, H; Olliff, S; Lester, W; Chen, F; Martin, B; Knox, E; Johnston, T; Elliot, C
Abstract : Introduction: Budd–Chiari syndrome (BCS) is a rare disease that mainly affects young women. Pregnancy is a prothrombotic state which is likely to increase adverse outcome in patients with BCS. The aim is to study the outcome of pregnancy in patients with BCS to allow patients to understand the risks that may be associated. Methods: A retrospective study of pregnancy in women with known and treated BCS at a single tertiary care centre from January 2001 to December 2015. Results: Out of 53 females, seven women had 16 pregnancies. At least one causal factor for hepatic vein obstruction was identified in 6 women (86%). 6 women had undergone radiological decompressive treatment for BCS. All patients had anticoagulation and it was continued during all pregnancies. 6 foetuses were lost before 20 weeks gestation in 2 women. There were 9 deliveries over 32 weeks gestation and one delivery before 32 weeks (27 weeks of gestation). All infants did well. Seven patients needed emergency caesarean sections for different reasons. There were no cases of thrombosis. Two patients had noteworthy vaginal (PV) bleeding in three pregnancies. None of the patients had variceal haemorrhage. Two patients were diagnosed with pulmonary hypertension, one during pregnancy and the other in post-partum period. There was no maternal mortality. Conclusion: Maternal outcome in patients with controlled BCS is generally good though majority of patients needed caesarean section. Fetal outcome beyond 20 weeks gestation is also good. Pregnancy should not be contraindicated in these patients and they should be managed in centres experienced in treating high-risk pregnancies with multi-disciplinary approach. Screening echocardiography to detect pulmonary hypertension should be considered in such patients. Disclosure of Interest: None Declared